(3eNJUQ aj Yde GdCNdGbs - (3eLghds ((3dWa Gddgs)
(3ChdgG (B:s
(3GdNdb edcI jUOQ YfgG GdCaYGd GdfaSGfjI HSghdI ef ZjQ QhjI(B...s
(3BNQgG (B:s
(3hGdTabI Ydjge, hEYWGA GdSGFd EPG CdM (B... (3hEXgGQ GdaQM daQMge hGdZe dZege CeG HMjK dG jNQL Edi MO GdfaGbs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs